Strategi Pengembangan Seni Kriya Gerabah: Analisis Triple Helix di Desa Wonorejo Pekalongan - Marotina, R. Nia; Bariki, Yusril (YASIN, 2024)
Wonorejo Village is one of the creative economy icons of Pekalongan Regency and the largest pottery village in Central Java. This research aims to analyze the strategy for developing the creative economy among pottery craftsmen in Wonorejo Village and the strategy used in developing this creative economy is the Triple Helix method. This research uses data collection in the form of qualitative methods by conducting observations and interviews. The results of this research show that pottery craftsmen in Wonorejo Village experienced a decline in production due to a lack of promotional strategies and product innovation, which had an impact on the sustainability of the business being run. Based on this decline, there needs to be creativity and innovation in various things to increase the production volume of this pottery business. So it can be concluded that the creative economic strategy using the Triple Helix method in the pottery business can be carried out in various ways, either by increasing promotions, determining market targets, as well as collaborating with cultural and educational services to collaborate with schools or related agencies for educational tourism. is in Central Java and D.I. Yogyakarta.